2017
DOI: 10.1097/brs.0000000000001662
|View full text |Cite
|
Sign up to set email alerts
|

Routine Use of Intraoperative Neuromonitoring During ACDFs for the Treatment of Spondylotic Myelopathy and Radiculopathy Is Questionable

Abstract: Study Design A retrospective database study. Objective The goal of this study was to (1) evaluate the trends in the use of intraoperative neuromonitoring (ION) for anterior cervical discectomy and fusion (ACDF) surgery in the United States and (2) assess the incidence of neurological injuries after ACDFs with and without ION. Summary of Background Data Somatosensory-evoked potentials (SSEPs) and motor-evoked potentials (MEPs) are the commonly used ION modalities for ACDFs. Controversy exists on the routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
2
31
1
Order By: Relevance
“…In a retrospective analysis of 720 patients, Traynelis et al 3 concluded that surgical decompression and reconstruction for symptomatic cervical spine disease may be safely performed without utilizing IONM. In line with this study, Ajiboye et al 4 also found no benefit of IONM in the prevention of new postoperative neurological complications after anterior cervical surgery.…”
Section: The Use Of Ionm During Cervical Spine Surgerysupporting
confidence: 85%
“…In a retrospective analysis of 720 patients, Traynelis et al 3 concluded that surgical decompression and reconstruction for symptomatic cervical spine disease may be safely performed without utilizing IONM. In line with this study, Ajiboye et al 4 also found no benefit of IONM in the prevention of new postoperative neurological complications after anterior cervical surgery.…”
Section: The Use Of Ionm During Cervical Spine Surgerysupporting
confidence: 85%
“…However, multiple studies have suggested that neuromonitoring effects may have limited benefits in relatively simple spine surgeries. Neuromonitoring use in single-level spinal procedures showed decreased neurologic complications only among lumbar laminectomies without any significant improvement in anterior cervical discectomy and fusions (ACDF), lumbar fusions, or lumbar discectomies (23,25,26). Furthermore, neuromonitoring use in minimally invasive 1-and 2-level transforaminal lumbar interbody fusions did not decrease the incidence of malpositioned pedicle screws (27).…”
Section: Resultsmentioning
confidence: 99%
“…IOM was used in 2627 patients (17.1%), and there was a significant decrease in the use of ACDF from 22.8% in 2007 to 4.3% use in 2014. [1] In addition, another group of authors has performed a systematic search to identify studies on IOM use for anterior cervical spine surgery, and they limited usefulness for IOM for ACDF as there was no difference in the risk of neurological injury with or without IOM. [2] Cost-benefit relation A point of permanent debate is the cost-benefit relation of IOM.…”
Section: Iom In Cervical Pathologymentioning
confidence: 99%